Are Sitting Position and Working Duration Associated with Low Back Pain in Workers?: A Meta-Analysis - Herawati Prianggi; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, 2021)
Background: Low back pain (LBP) is general